Black male fiction and the legacy of Caliban - Coleman, James W. (James Wilmouth), 1946-2019 (University Press of Kentucky, 2001)
With The Tempest's Caliban, Shakespeare created an archetype in the modern era depicting black men as slaves and savages who threaten civilization. As contemporary black male fiction writers have tried to free their subjects and themselves from this legacy to tell a story of liberation, they often unconsciously retell the story, making their heroes into modern-day Calibans. Coleman analyzes the modern and postmodern novels of John Edgar Wideman, Clarence Major, Charles Johnson, William Melvin Kelley, Trey Ellis, David Bradley, and Wesley Brown. He traces the Caliban legacy to early literary in.